Association of caries experience and dental plaque with sociodemographic characteristics in elementary school-aged children: a cross-sectional study - Saeed Bashirian; Samaneh Shirahmadi; Shabnam Seyedzadeh-Sabounchi; Ali Reza Soltanian; Akram Karimi-shahanjarini; Farshid Vahdatinia (BMC, 2018)
Abstract Background Dental caries among Iranian elementary school children aged 6-12 years continue to rise. To estimate treatment needs and guide health initiatives, current epidemiologic data are required. Such data are currently unavailable for dental health. The purpose of this study was to assess caries experience, dental plaque, and associated factors in elementary school-aged children from Iran. Methods In this cross-sectional study, 988 elementary school children aged 7-12 years were selected by multistage cluster sampling. Dental caries was studied using the WHO criteria, dental plaque was examined according to O'Leary index. Data on parental education and occupation, living district, dental pain within the past year, and tooth brushing habits under parental supervision were collected through interviews based on questionnaire. The data were analyzed with descriptive statistics and logistic and linear regression. Results The mean (SD) age of the elementary school children was 9.64 (1.73) years. The highest dmft was seen in elementary school children aged 7-8 years 6.53 (4.37) and the highest DMFT and dental plaque was in 12 year olds recorded as 1.17 (1.77) and 51.97 (25.86), respectively. The proportion of decayed teeth in 7 years old elementary school based on dmft index was 80.36%, moreover, the proportion in 12 years old elementary school was 40.17% based on the DMFT index. Age, gender, and dental pain within the past year were significantly associated with DMFT and dmft. The odds of developing dental caries (DMFT) was 1.70 times higher in girls than in boys (p < 0.001) and 1.72 times higher in the students that reported dental pain frequently than in those who did not (p = 0.005). The chance of developing dental caries (dmft) was 0.47 times lower in girls than boys (p < 0.001). Age was significantly correlated with dental plaque such that Plaque Index increased by 2.44 times per one year increase in age (p < 0.001). Conclusion Results indicated that dental caries experience and plaque formation among elementary school children in Hamadan were high and they were influenced by their sociodemographic factors. The associations found can be used as a helpful guide for planning accurate preventive programs for elementary school children in this region.